The Energy Nexus Group – An Interdisciplinary Research Agenda. (August 2016) - Cader, Catherina; Daykova, Mariana; Dumitrescu, Raluca; Pelz, Setu; Koepke, Mathias
Abstract: This paper introduces a new, transformative energy research agenda. A group of researchers has developed a novel approach to tackle the particularities of energy access development in the Global South from a nexus perspective. An interdisciplinary team will use a set of common and specific action-oriented methodologies in order to find sustainable, cross-sector solutions to the pressing issues in energy access with a strong focus on Africa and Asia. Investigating a range of cross-sectoral thematic areas including technology, finance, agriculture, water and policy at decentralized scales, the group draws holistic conclusions from systemic analysis of inherent co-dependencies and causalities. It is argued that next-generation energy access solutions will need to incorporate the relations to other spheres of influence linked to the energy field. This is required in order to create an understanding of challenges, working mechanisms and best practices to systematically address the complex issue of energy access for long-term, scalable impact. The research will thus create a unique platform for knowledge exchange between experts with diverse backgrounds and origins. Solutions will be adapted to local and regional circumstances by incorporating information exchange between institutions from different countries and regions (South-South learning) as well as the sensitive inclusion of feedback from researched communities.